STRATEGI PENGEMBANGAN INDUSTRI MEUBEL ROTAN IRMA JAYA DI KOTA PALU - Idris, Mariani (AGROTEKBIS, 2015)
The purpose of this  study was to analysis the strategy of ?Irma Jaya Rattan Furniture?. SWOT was used to analyse the collected data. The results showed that Irma Jaya Rattan the development influenced by internal and external factors. Internal factors had a total value of 3.61 with scores of strength 2.59 and weakness 1.02, respectively. This shows the strength factor was greater than the weakness, while external factors have a total value of 2.61 with scores of opportunities 2.04 and threat 0.57, respectively. This showed that the opportunities factor was greater than the threat. Therefore the suitable alternative strategies for the development of Rattan Furniture Industry Irma Jaya is by using SO, Irma Jaya Rattan Furniture Industry can create a strategy that uses force to take advantage of existing opportunities.